Material properties and compressive local buckling response of high strength steel square and rectangular hollow sections. (1st January 2017) - Wang, J.; Afshan, S.; Schillo, N.; Theofanous, M.; Feldmann, M.; Gardner, L.
Highlights: Experimental investigation into the structural performance of compressed high strength steel (HSS) square and rectangular hollow sections. Tensile coupon tests, measurements of geometric imperfections, full cross-section tensile tests and stub column tests. Assessment of the Eurocode 3 design guidelines for high strength steels. Assessment of material ductility requirements, the Class 3 slenderness limit for internal elements in compression and the effective width formula for Class 4 internal elements in compression. Reliability analysis of design recommendations. Abstract: An experimental investigation into the structural performance of compressed high strength steel (HSS) square and rectangular hollow sections is described in this paper. Both hot-rolled and cold-formed HSS sections were examined. In total six S460NH and five S690QH hot-rolled section sizes and three S500MC, two S700MC and four S960QC cold-formed section sizes were tested. The experimental programme comprised tensile coupon tests on flat and corner material, measurements of geometric imperfections, full cross-section tensile tests and stub column tests. The results of the experiments presented in this paper have been combined with other available test data on high strength steel sections, and used to assess the existing design guidelines for high strength steels given in Eurocode 3. The focus has been on the material ductility requirements, the Class 3 slenderness limit for internal elements in compression and the effective width formula for Class 4 internal elements in compression.Reliability assessments of the Class 3 slenderness limit (both the current value of 42 and a proposed value of 38) and the effective width formula for Class 4 internal elements in compression were carried out. The analysis indicated that, based on the assembled test data considered in this study, and the assumptions made regarding the statistical distributions of material and geometric properties, a partial safety factor greater than unity is required for HSS. Similar findings have also recently been presented for ordinary strength steels.